Antifungal activity of schinol and a new biphenyl compound isolated from Schinus terebinthifolius against the pathogenic fungus Paracoccidioides brasiliensis - Cota Betania B; Cisalpino Patricia S; Lima Luciana ARS; Sá Nívea P; Johann Susana; Alves Tânia MA; Siqueira Ezequias P; Zani Carlos L (BMC, 2010)
Abstract Background The aim of this study was to isolate and identify the antifungal compounds from the extracts of Schinus terebinthifolius (Anacardiaceae) against clinical isolates of the pathogenic fungus Paracoccidioides brasiliensis. Methods The hexane and dichlomethane fractions from leaves and stems of S. terebinthifolius were fractionated using several chromatography techniques to afford four compounds. Results The compounds isolated from S. terebinthifolius were identified as schinol (1), a new biphenyl compound, namely, 4'-ethyl-4-methyl-2,2',6,6'-tetrahydroxy[1,1'-biphenyl]-4,4'-dicarboxylate (2), quercetin (3), and kaempferol (4). Compounds 1 and 2 were active against different strains of P. brasiliensis, showing a minimal inhibitory concentration value against the isolate Pb B339 of 15.6 μg/ml. The isolate Pb 1578 was more sensitive to compound 1 with a MIC value of 7.5 μg/ml. Schinol presented synergistic effect only when combined with itraconazole. The compounds isolated from S. terebinthifolius were not able to inhibit cell wall synthesis or assembly using the sorbitol assay. Conclusion This work reveals for the first time the occurrence of compound 2 and discloses activity of compounds 1 and 2 against several clinical isolates of P. brasiliensis. These results justify further studies to clarify the mechanisms of action of these compounds.